BIM Application to Select Appropriate Design Alternative with Consideration of LCA and LCCA. (29th September 2015) - Shin, Young-su; Cho, Kyuman
Abstract : Advancements in building materials and technology have led to the rapid development of various design solutions. At the same time, life cycle assessment (LCA) and life cycle cost analysis (LCCA) of such solutions have become a great burden to engineers and project managers. To help conduct LCA and LCCA conveniently, this study (i) analyzed the information needed to conduct LCA and LCCA, (ii) evaluated a way to obtain such information in an easy and accurate manner using a building information modeling tool, and (iii) developed an Excel spreadsheet-based framework that allowed for the simultaneous implementation of LCA and LCCA. The framework developed for LCA and LCCA was applied to a real building case to evaluate three possible alternatives for an external skin system. The framework could easily and accurately determine which skin system had good properties in terms of the LCA and LCCA performance. Therefore, these results are expected to assist in decision making based on the perspectives of economic and environmental performances in the early phases of a project, where various alternatives can be created and evaluated.